THE IMPLEMENTATION OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TO MOTIVATE STUDENTS’ SPEAKING ACTIVITY - Nur Halimah; Lies Kryati; Indah Wardaty Saud; Dewi Paputungan (Institut Agama Islam Negeri (IAIN) Manado, 2021)
The purpose of this research was to find out whether the implementation of Student Team Achievement Division (STAD) able to motivate students’ speaking activity or not. The researcher used classroom action research design in this study. The subject was the class VIII B of eighth grade students of SMP Negeri 1 Sangkub consisting on 25 students which comprised 12 females and 13 boys. In this present research, the researcher used some instruments to collect the data, such as; Lesson Plan (RPP), Tests, observation, Interview, and documentation. In applying the test, the researcher asked the subject under the research to practice a simple dialogue about expression of giving instruction and expression of asking permission.In this research, there were three cycles, namely; Pre-Cycle, Cycle I, and Cycle II. Furthermore, Cycle I and II consisted on two sessions. In Pre-Cycle, the completeness percentage was low (36%) so that the present classroom action study was conducted to solve the problems of the students. The result of Cycle I showed that STAD motivated students’ speaking activity. It could be seen from the increase of the completeness percentage of Cycle I (64%). The researcher continued the research by conducting the Cycle II to revise the problem in Cycle I and the completeness percentage of Cycle II was (88%). Based on the result above, the STAD technique has a positive influence to students of class VIII B at eighth grade students of SMP Negeri 1 Sangkub speaking activity, and this STAD Technique could be used to be one of the alternative teaching techniques. Key Words: STAD, Motivate, Speaking Activity.